Atom interferometry in an Einstein Elevator - C. Pelluet; R. Arguel; M. Rabault; V. Jarlaud; C. Métayer; B. Barrett; P. Bouyer; B. Battelier (Nature Communications)
Abstract Recent advances in atom interferometry have led to the development of quantum inertial sensors with outstanding performance in terms of sensitivity, accuracy, and long-term stability. For ground-based implementations, these sensors are ultimately limited by the free-fall height of atomic fountains required to interrogate the atoms over extended timescales. This limitation can be overcome in Space and in unique “microgravity” facilities such as drop towers or free-falling aircraft. These facilities require large investments, long development times, and place stringent constraints on instruments that further limit their widespread use. In this work, we present a new approach in which atom interferometry is performed in a laboratory-scale Einstein Elevator. We demonstrate an acceleration sensitivity of 6 × 10−7 m/s2 per shot, with a total interrogation time of 2T = 200 ms. We further demonstrate the capability to perform long-term statistical studies by operating the Einstein Elevator over several days with high reproducibility.